Pengaruh Media Gambar terhadap Minat Belajar Siswa di IPA Kelas Atas SD - Permadi, Benny Angga; Siptiani, Eka; Alai, Ashimatul (Universitas KH. Abdul Chalim Pacet Mojokerto, 2024)
Picture media is a tool that can be effectively used by teachers in the learning process to create meaningful learning experiences for students. A teacher's expertise, accuracy, and ability to utilize this media significantly influence students' interest in learning. This study is an ex post facto research with a quantitative approach. The population in this study consisted of all upper-class students at SDN Mojokembang, with the sample covering all population members. Data collection techniques included questionnaires and documentation. This study aims to determine whether the use of picture media positively affects students' interest in learning science in the upper classes (IV, V, VI) at SDN Mojokembang. The results of the hypothesis test analysis show a value of r = 0.709. The results are declared significant since the F value of 106.737 is greater than the F table value of 1.80. Additionally, the significance test shows that the t value of 9.854 is greater than the t table value of 1.6743, leading to the rejection of H0 and acceptance of Ha. This study proves that there is a positive effect of using picture media on students' learning interests. It can be concluded that there is a positive influence between the use of picture media and students' learning interest in the upper classes (IV, V, VI) of SDN Mojokembang in the 2023/2024 academic year.